Design of solar powered light for remote country with poor lighting / Muhammad Imran Roslan - Roslan, Muhammad Imran (2022)
A Solar panel is a panel that use renewable resources to create energy that helps a lot of people by providing electricity. This is a green technology because it does not produce any emission of any kind of smoke. It creates energy by using photovoltaic module or more known as solar panel that depends on irradiance that reach the solar cells and charge the battery for certain projects. Many factors contribute the parameters which directly affect the solar panel. Solar panel utilization is a very practical way to produce electricity for many applications. Off-grid living means living in a location that is not serviced by the main electric conventional source of electricity energy, people need to pay high-cost fees for installation but not in this case. Because we only use a small portion of solar panel to utilize it and it only use a basic circuit that could help how the solar panel works. The method that are used to fabricate this prototype is Solidworks 2017 to show how it going to look like and how it is going to work and to attract any investor that would help in this prototype. In conclusion, it is not too late for us to convert from using coal power to solar power by introducing this product to everyone. This product can be improvised by professional helps and it also a helps earth from global warming by reducing the emission of coal power plant or any type of power plant that exist and the recommendation for this prototype is for this project, I would recommend for it to able to turn it off automatically by using some sort of sensor or apps that could be applied. We can use a Li-ion Battery to save up some of the solar power that were stored. So, this product could be help if more knowledge or research were made and there should not be a problem when doing this project